Evaluasi Pasca Implementasi SAP pada Departemen PPIC PT. X - Sugianto, Jessica; -, Felecia (Jurnal Titra, 2013)
PT. X is a manufacturing company with flexible film packaging products. The companyâs SAP system application was about to change intonthe new SAP system. The Evaluation of the SAPâs new post-implementation can be done in 2 ways. The first way is to describe the new SAP systemâs adventages, compared to the old SAP system. The oter way is to do an evaluation of the potential problems and providing solutions to the problems. The results of the evaluation stated that there are 2 new SAP adventages, compared to the old SAP. The first adventage is thatvthe new SAP system can separate the plastic waste generated by the type of waste. The other adventage is that the system of naming batches on the new SAP was more effective. The results of subsequent evaluation stating that there are 2 new SAP post implementation problems. The first problem is an error in the SO making process. The solutions that can be given is to seek approval from the marketing for the SO to be processed, as well as changing the SO data input system. The other problem is the staff that arenât executed the system of export orders. The solution that given is make the new approval system for the eksport layout images.